Lung cancer screening by low-dose CT among asbestos-exposed workers: first results of a pilot program. (13th November 2019) - Heidrich, J; Wolff, C; Centmayer, A; Wiethege, T; Duell, M; Taeger, D; Harth, V
Abstract: Background: Occupational asbestos exposure (OAE) is a risk factor for lung cancer (LC) and can cause malignant diseases decades after exposure. Lung cancer screening with low-dose computed tomography (LCS) in heavy smokers has shown LC-mortality reductions in two large trials. Recent guidelines advocate LCS in high-risk populations with OAE and additional smoking history. Methods: A structured pilot program on LCS in three German regions has been implemented from 2014 to 2018. Eligibility criteria are: OAE ≥10 years starting before 1985 or diagnosis of OAE-related lung disease other than cancer, age ≥55 years and smoking history ≥30 pack years. Eligible persons are centrally invited for LCS on a voluntary basis in 12 months intervals. All persons willing to participate receive obligatory physician counselling before LCS. CT scans are performed according to a standardized protocol. The program provides technical quality assurance as well as independent double reading of all suspicious findings and of a random sample of all CT scans. Results: Of 2715 and 1534 persons invited to first and second LCS, 1571 (57.9%) and 715 (46.6%) agreed to participate, respectively. Main reason for disagreement was principal refusal of LCS (15.5% in first and 22.2% in second LCS), whereas 8.5% and 6.9%, respectively, refused after counselling. Additionally, 12.9% and 5.7% did not respond at all. Effectively, 68.8% and 70.6% of those who initially agreed, received first and second LCS, respectively. Variations between regions were observed (range 61.0% to 79.8%). First preliminary outcome assessment shows detection rates of 0.019 and 0.011 in first and second LCS, respectively. Conclusions: A substantial group of eligible persons with OAE participated in LCS after physician counselling. Participation remained stable over two screening rounds. First results show detection of LC in the expected range. The effectiveness of early detection of LC in OAE needs to be evaluated further. Key messages: Participation over the first two screening rounds in structured lung cancer screening remained stable among eligible persons with OAE and smoking history who were counselled by physicians. Detection of lung cancer in a structured pilot screening program in three German regions seems to be within the range to be expected from previous research.